Pembuatan dan Karakterisasi Karbon aktif dari Pelepah Kelapa Sawit dengan Aktivasi Ultrasonik sebagai Adsorben Rhodamin B - Fajar Sa'bandi; Syamsi Aini; Umar Kalmar Nizar; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2021)
The manufacture of activated carbon from oil palm frond waste using an ultrasonic wave activator has been successfully carried out. The carbonization process was carried out at a temperature of 250ºC for 90 minutes. Activation with ultrasonic waves (35 Watt, 40 KHz) for 30 minutes was able to increase the iodine number from 330.06 mg/g to 799.14 mg/g and was in accordance with SNI No.06-3730-1995. FTIR spectra show that the activated carbon of oil palm fronds has a functional group –OH at wave number 2900-3200 cm-1, C=C at wavenumber 1500-1600 cm-1, C-O at wavenumber 1200-1250 cm-1. The results of the adsorption test on Rhodamine B dye showed that the activated carbon produced had an optimum absorption capacity of 9.04 mg/g at a concentration of 400 ppm for 90 minutes. Studies show that the adsorption isotherms absorption mechanisms tend to follow the Freundlich equation with a correlation coefficient (R2)= 0.9861.